Multifocal fixed drug eruption with COX-2 inhibitor-celecoxib - Shikha Chugh; Rashmi Sarkar; Vijay K Garg; Avninder Singh; Chitralekha Keisham (Wolters Kluwer Medknow Publications, 2013)
Cyclooxygenase-2 (COX-2) inhibitors are rapidly becoming the first choice nonsteroidal anti-inflammatory drugs (NSAIDs) for various rheumatological and other painful conditions. However, they might not be as safe or free of side effects as they are considered to be. These COX-2inhibitors may cause a variety of dermatological and systemic side effects of which we should be aware to avoid their indiscriminate use. We hereby report a case of multifocal fixed drug eruption (FDE) with celecoxib which has not yet been reported in Indian settings.